Investigation of the Alleged Corruption Case in the Rp 9.9 Trillion Education Laptop Procurement Budget: An Analysis of the Rp 10 Million Per-Unit Laptop Acquisition During Nadiem Makarim’s Tenure - Fitriyani Farida (Eduvest - Journal of Universal Studies, 2026)
The case of alleged corruption in the procurement of Chromebook-based laptop devices within the Education Digitalization Program at the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) for the 2019–2022 period, with a total budget of IDR 9.9 trillion, has attracted public attention. This research aims to evaluate the mechanism of laptop procurement, detect indications of irregularities, analyze the factors contributing to corruption, and discuss its impact on budget efficiency, accessibility, and the quality of education. This study adopts a qualitative approach using a case study methodology. Data are collected from procurement documents, media reports, and relevant legislation. Data analysis is conducted through content analysis to identify indications of irregularities, such as price mark-ups, collusion, fictitious procurement, and deviations from specifications. The findings indicate that the procurement mechanism is allegedly inconsistent with the principles of good procurement, alongside alleged “malicious collusion” leading to the use of the Chromebook operating system. The investigation process by the Attorney General’s Office (Kejagung) is still ongoing, with witness examinations and seizures already carried out. This research is expected to contribute to the eradication of corruption in the education sector and produce policy recommendations that support better governance and accountability.